Chromatin landscape and endocrine response in breast cancer. (December 2012) - Magnani, Luca; Brunelle, Mylène; Gévry, Nicolas; Lupien, Mathieu
Over two-thirds of breast cancers rely on estrogen receptor α (ERα) for their growth. Endocrine therapies antagonize estrogen-dependent ERα activation but resistance to these treatments occurs and is associated with poor prognosis. Crosstalk between alternative survival pathways and ERα are currently held as the primary cause of resistance. However, blocking these pathways does not cure endocrine therapy resistant breast cancer suggesting the existence of additional mechanisms. While cancer is commonly considered a genetic disease, the importance of epigenetic events in promoting tumor initiation and progression is increasingly recognized. Here, we consider how epigenetic modifications and alterations to the chromatin landscape contribute to endocrine therapy resistance by modulating ERα expression or altering its genomic activity.